COMPARATIVE STUDY ON PERMIAN BASALTS FROM EASTERN XINJIANG-BEISHAN AREA OF GANSU PROVINCE AND ITS TECTONIC IMPLICATIONS - Zhao Z.H.; Wang Y.; Guo Z.J.; Han B.F.; Liu C. (My University, 2006)
After comparing study on Permian basalts from Stantanghu basin eastern of Xinjiang and Liuyuan area of Beishan western of Gansu, on the basis of geochemical characteristics, it is concluded that nearly synchronogenic basalts from Permian fault basins of eastern Xinjiang-Beishan area have different geochemical characteristics and magma sources. A united dynamic model is presented, which is that eastern Xinjiang-Beishan area was under the rift-extensional tectonic setting in early Permian which might be a result from both upwelling of partial melting asthenospheric mantle induced by delamination of thickened subcontinental mantle root, and upwelling of small mantle plume from the boundary between upper mantle and lower mantle. This kind of small mantle plume is not from boundary between core and mantle, but may be from boundary between upper mantle and lower mantle where partial melting of pyrolites brought about after subducted oceanic crust fell down. In Permian, upwelling of partial melting asthenospheric mantle induced by delamination of thickened subcontinental mantle root and upwelling of small mantle plume from the boundary between upper mantle and lower mantle was likely the most magnificent crust-mantle interaction that made Central Asian Orogenic Belt (CAOB) distinguished from other orogenic belts, with intense basalt eruption, formation of fault basins, prominent metallogenesis, and emplacement of voluminous granitic and mafic-ultramafic rocks with positive εND (t).
Keywords: BASALT; COMPARATIVE STUDY; EASTERN XINJIANG-BEISHAN AREA OF GANSU; PERMIAN; TECTONIC IMPLICATION; Палеозой::Пермская; Paleozoic::Permian